2015
DOI: 10.1080/09168451.2015.1060845
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the plasma amino acid profile by leucine via the system L amino acid transporter

Abstract: Plasma concentrations of amino acids reflect the intracellular amino acid pool in mammals. However, the regulatory mechanism requires clarification. In this study, we examined the effect of leucine administration on plasma amino acid profiles in mice with and without the treatment of 2-aminobicyclo-(2,2,1)-heptane-2-carboxylic acid (BCH) or rapamycin as an inhibitor of system L or mammalian target of rapamycin complex 1, respectively. The elevation of plasma leucine concentration after leucine administration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The BCAA and aromatic AA including Tyr, Tryptophan (Trp), and Phe share the same AA transport system across the plasma membrane, known as system-L AA transporters (LAT). The LAT system is a Na+-independent AA transporter that mediates transport of other neutral AA, including several essential AA [13,35]. The role of LAT in the regulation of Leu-induced alterations in the plasma AA profile has been recently demonstrated in mice [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The BCAA and aromatic AA including Tyr, Tryptophan (Trp), and Phe share the same AA transport system across the plasma membrane, known as system-L AA transporters (LAT). The LAT system is a Na+-independent AA transporter that mediates transport of other neutral AA, including several essential AA [13,35]. The role of LAT in the regulation of Leu-induced alterations in the plasma AA profile has been recently demonstrated in mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…The LAT system is a Na+-independent AA transporter that mediates transport of other neutral AA, including several essential AA [13,35]. The role of LAT in the regulation of Leu-induced alterations in the plasma AA profile has been recently demonstrated in mice [13]. They found that the elevation of plasma Leu concentration lead to a decrease in the plasma concentrations of Ile, Val, Met, Phe, and Tyr; and that LAT is involved in the mechanism of Leu action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imbalances between branched-chain amino acids have been reported by other authors to have undesirable metabolic effects in patients with PA and MMA (26). Also, excess Leu was found to reduce plasma Val and Ile by interfering with the LAT1 transport of amino acids (27). In addition, animals fed high doses of Leu show low central nervous system concentrations of tryptophan (Trp), Val, Ile, Met and low brain alanine (Ala), which might affect the synthesis of neurotransmitters (28).…”
Section: Discussionmentioning
confidence: 78%